2020
DOI: 10.1029/2019je006160
|View full text |Cite
|
Sign up to set email alerts
|

Climate Simulations of Early Mars With Estimated Precipitation, Runoff, and Erosion Rates

Abstract: The debate over the early Martian climate is among the most intriguing in planetary science. Although the geologic evidence generally supports a warmer and wetter climate, climate models have had difficulty simulating such a scenario, leading some to suggest that the observed fluvial geology (e.g., valley networks, modified landscapes) on the Martian surface could have formed in a cold climate instead. However, as we have originally predicted using a single‐column radiative‐convective climate model (Ramirez, K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 168 publications
(532 reference statements)
8
30
0
Order By: Relevance
“…These results support a recent study by Ramirez et al. (2020), which showed that warming from CO 2 ‐H 2 CIA would likely be between the extremes of using N 2 ‐H 2 CIA and the CIA values from Wordsworth et al. (2017).…”
Section: Implications For Ancient Marssupporting
confidence: 90%
See 2 more Smart Citations
“…These results support a recent study by Ramirez et al. (2020), which showed that warming from CO 2 ‐H 2 CIA would likely be between the extremes of using N 2 ‐H 2 CIA and the CIA values from Wordsworth et al. (2017).…”
Section: Implications For Ancient Marssupporting
confidence: 90%
“…The temperatures are still higher than those derived in Ramirez et al (2014), using the weaker N 2 CIAs, which would require 3-4 bar total pressure to achieve the same temperatures. These results support a recent study by Ramirez et al (2020), which showed that warming from CO 2 -H 2 CIA would likely be between the extremes of using N 2 -H 2 CIA and the CIA values from Wordsworth et al (2017). Mean surface temperatures above 273 K can be reached with the new CIA if surface pressures exceed ∼3 bar for a 10% CH 4 atmosphere or with 5% hydrogen and less than 2 bar of surface pressure.…”
Section: Climate Model Detailssupporting
confidence: 88%
See 1 more Smart Citation
“…Many investigators believe that ancient Mars was wet and habitable (Ehlmann et al 2011;Fairén 2020;Squyres and Knoll 2006;McKay 2010;Vago and Westall 2017;Grotzinger et al 2014;Jaumann et al 2014), and that in addition to thousands of lakes, oceans of water were at least temporarily present (Duxbury 2000;Fawdon et al 2018;Parker 1986;Head et al 1999;Ivanov et al 2014;Dickeson and Davis 2020;Fairén et al 2003). However, if ancient Mars had a stable, long-duration Earth-like ocean is subject to considerable debate and no clear consensus has emerged, except in regard to the generally agreed belief that oceans of water may have flowed across the surface of the northern hemisphere (Ramirez et al 2020;Carr and Head 2019;Dickeson and Davis 2020) What became of the Martian lakes and its oceans of water is also subject to much debate; though one contributing possibility may be abiotic photosynthesis. If over the course of the last 4 billion years the production of atmospheric oxygen has been completely abiotic, then this would have resulted in the complete evaporation of a planet-wide ocean of water with an initial depth of 50 to 80 meters (Barth 1974;Zhang et al 2012).…”
Section: Subglacial Lakes Oceans Oxygen and Abiotic Photosynthesismentioning
confidence: 99%
“…The "cold and frozen" camp credits melting ice with scooping out the valleys. Now, new research (1) suggests that a large ocean was indeed required to form the features across the planet's surface. But rather than warm and wet, the planet would have been cool and semi-arid.…”
mentioning
confidence: 99%